Lassoed and Branded: The Calgary Exhibition and Stampede and the City of Calgary, 1889-1976 - Foran, Max (Urban History Review / Revue d'histoire urbaine, 2006)
There is a complex relationship between the Calgary Exhibition and Stampede (Stampede) and the City of Calgary, On the one hand, the Stampede depends on the municipal government for its very existence. On the other, its arm's-length structure and success in attracting power and influence lend an independence more typical of a private corporation. Since both agree on the value of the Stampede to the City, relations between the two have been far more co-operative than strained. However, in the two instances of public controversy over decisions made by both, the City has allowed the Stampede to take the burden of blame, with the result that the public's image of the Stampede has blurred while its aura of independence has been enhanced.